Unpacking and Extending Moral Injury: Comments on Nielsen et al. (2024) - Crayne, Matthew P. (Journal of business ethics, 2026)
Moral injury is a unique form of psychosocial trauma caused by the violation of deeply held values. Predominantly studied in military and clinical psychology, recent calls for expansion to other fields have led to increased interest in organizational science. However, the general dearth of research and theory on moral injury in these disciplines has created space for prior literature to be misunderstood or misrepresented in a way that could unintentionally dilute the construct and thereby future research. Such is the case, in my view, of a recent qualitative study by Nielsen and colleagues (Journal of Business Ethics 194:233-249). In this commentary, I articulate what I see as several critical misalignments between this study and established moral injury theory and research. In doing so, I aim to provide conceptual clarity on what moral injury is versus what it is not, focused on construct validity and the appropriateness of measurement. I engage with these issues to add additional context and consistency to this growing literature. I conclude my comments noting several positive and additive contributions of this work, as well as my view of future directions for moral injury research in organizational science.